Qui connaît le Casier archéologique et artistique (1916-1928) ? - Laurence Bassières (In Situ)
The Casier archéologique et artistique, an architectural and urban inventory of Paris and the former department of the Seine, which was compiled between 1916 and 1928, enjoyed a certain amount of recognition during its development and during the following decade, before becoming widely forgotten in the 1940s. This inventory, conceived in the perspective of what was already known as “Grand Paris” and which gave rise to the creation of nearly two thousand files and more than six thousand photographs, was launched on the initiative of the architect Louis Bonnier (1856-1946), who directed its entire elaboration and mobilized many protagonists, members of the Commission du Vieux Paris, architects and surveyors of the Directorate of Architectural Services and photographers. Some of them, or their contemporaries, made considerable efforts to publicize the Casier, with varying degrees of success: in addition to an unsuccessful attempt to publish the photographs and a small number of articles on the subject, other means of dissemination (minutes of the Old Paris Commission, conferences, etc.) played an important role in this undertaking. The aim here is to examine the various means used to make this inventory known and to highlight their role in its recognition, from its relative notoriety to its erasure.